Prevalence and Epidemiology of Bacterial Wilt of Tomato - Sood, Deepika; Sharma, Amit; Sharma, Monica (International Journal of Economic Plants, 2022)
The present investigation was carried out during 2017 at the Department of Plant Pathology, Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan. The objective of the study was to understand the prevalence of bacterial wilt of tomato as influenced by the edaphic factors. Periodic survey were undertaken during the crop season in major tomato growing regions and incidence of bacterial wilt of tomato ranged from 10.00% to 84.02%. 20 days old tomato seedlings were inoculated with bacterial suspension (3x108 cfu/ml) either through root dip or drenching and kept in green house with temperature 30+2°C. Inoculation of bacterial pathogen R. solanacearum in through seedling root dip in bacterial suspension was found better compared to drench application for development of typical symptoms of bacterial wilt disease. There was 100% disease incidence with seedling root dip method compared to 68.74% disease incidence with drenching of bacterial suspension in soil. Epidemiological studies of R. solanacearum revealed that with the increase in soil moisture from 40% to 90%and soil temperature from 25° to 35°, there was a progressive increase in disease incidence of bacterial wilt in tomato seedlings. Maximum disease incidence was observed at 30–35°C and at 90% soil moisture. However, no disease was observed at 20°C and at 20% and 30% soil moisture. The finding on epidemiology from the present study will be helpful to design effective disease management strategy.